Cassava Starch Edible Film Incorporated with Lemongrass Oil: Characteristics and Application - Supardan, Muhammad Dani; Annisa, Yulia; Arpi, Normalina; Satriana, Satriana; Wan Mustapha, Wan Aida (International Journal on Advanced Science, Engineering and Information Technology, 2016)
The objective of this research is to evaluate the effect of the addition of lemongrass essential oil (LGO) on the characteristics and antimicrobial properties of cassava starch based ï¬lms. Edible films were prepared from a mixture of cassava starch and glycerol. LGO was added to edible films as natural antimicrobial agent. There was a reduction in tensile strength of edible film because of incorporation of LGO. The presence of LGO also caused to a reduction in roughness of the edible film. The experimental results showed that Trichoderma and Penicillium was not appear upon the film until the third day of incubation. Meanwhile, the use of edible films containing LGO as antimicrobial agents caused to a reduction in microbial counts of meat during storage.